Pengaruh Lingkungan Kerja, Budaya Organisasi dan Work Life Ballance Terhadap Kepuasan Kerja Karyawan PT Supra Jaya Abadi Medan - Sevira, Wike; Wulandari, Niken; Malikhah, Ikhah (Indo-MathEdu Intellectuals Journal, 2025)
The research aims to determine whether the work environment, organizational culture, and work-life balance affect employee job satisfaction at PT Supra Jaya Abadi Medan. The data analysis technique used is a quantitative research method with the help of SPSS version 25. The sample in this study consisted of 75 respondents. Primary data was collected using a questionnaire. This study employs multiple linear regression analysis. The research results indicate that the work environment has no significant partial effect on job satisfaction. Organizational culture has a positive and significant partial effect on job satisfaction. Work-life balance has a positive and significant partial effect on job satisfaction. The calculated F value is 30.642, which is greater than 2.73, and the significance value is 0.000, which is less than 0.05. Therefore, it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected, so it can be concluded that the work environment, organizational culture, and work-life balance have a significant simultaneous effect on employee job satisfaction at PT Supra Jaya Abadi Medan.